2017
DOI: 10.1159/000477737
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dynamics of Mitotic Transition in B-Cell Lymphoma and Reactive B-Cell Lymphoproliferations Determined by H3S10 Phosphohistone Immunolabeling

Abstract: Objectives: Clonal selection in the follicular germinal centers in lymphatic tissues is accompanied by an intense proliferation of polyclonal B cells in a precisely regulated fashion. In contrast, B-cell neoplasias proliferate autonomously due to endogenous stimuli. The cell kinetic activity is obvious at many levels including progressive chromatin modification and elevated mitotic rates. We asked if there are differences in the kinetics of histone H3S10 phosphorylation required for mitotic entry between highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, the phosphorylation of histone 3 serine 10 (H3S10) is responsible for the immediate condensation of chromatin in the late G2 phase of the cell cycle and, thus, can function as a marker that is present only in dividing cells [ 119 ]. Indeed, the levels of phosphorylated H3 have been used to determine mitotic activity and to experimentally, as well as clinically, measure cellular proliferation in different cancer types, including lymphomas [ 120 , 121 , 122 ].…”
Section: Histone Modifications In Hematological Malignanciesmentioning
confidence: 99%
“…Additionally, the phosphorylation of histone 3 serine 10 (H3S10) is responsible for the immediate condensation of chromatin in the late G2 phase of the cell cycle and, thus, can function as a marker that is present only in dividing cells [ 119 ]. Indeed, the levels of phosphorylated H3 have been used to determine mitotic activity and to experimentally, as well as clinically, measure cellular proliferation in different cancer types, including lymphomas [ 120 , 121 , 122 ].…”
Section: Histone Modifications In Hematological Malignanciesmentioning
confidence: 99%
“…Thus, the discovery of compounds that target histone phosphorylation is an interesting approach for the treatment of oncological patients. In their study, Méhes et al [215] showed an enhanced G2 phase transition due to the abrupt chromatin phosphorylation in neoplastic B-cells. Moreover, during the Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 17 November 2021 G2 phase, phospho-H3 co-localizes with the Aurora B kinase which is known to be frequently overrepresented in NHL patients [216,217].…”
Section: Targeting Other Posttranslational Modifications Of Histonesmentioning
confidence: 94%
“…Phosphorylation of H3 at serine 10 (phospho-H3) results in immediate condensation of the chromatin in the late G2 phase of the cell cycle, and thus, is a marker present in dividing cells [ 207 ]. Indeed, mitotic activity determined by phospho-H3 counting has been experimentally and clinically used to measure cell proliferation in different types of cancer, including lymphoma [ 207 , 208 , 209 , 210 ]. Thus, the discovery of compounds that target histone phosphorylation is an interesting approach for the treatment of oncological patients.…”
Section: Targeting Histone Methylation and Some Other Ptmsmentioning
confidence: 99%